Kuliner Sunda di tengah laju modernitas: perkembangan rumah makan Sunda di Bandung tahun 1960-an hingga 2000-an - Alfonsus Tegar Setyawan; Azmah Sholihah; Siti Lilik Nur Rohmah (Historiography: Journal of Indonesian History and Education, 2022)
Bandung is one of the main culinary destinations in Indonesia. Bandung's culinary image has been rooted since the colonial era as Haryoto Kunto (1986) called Bandung “a hawker's paradise". A typical culinary of Bandung is Sundanese restaurants with its signature local dishes. Sundanese dishes usually served in a domestic environment (household). Since the 1960s to 1970s, there were trends of typical Sundanese food stalls in Bandung, namely Ampera, and Ponyo. Those were local people who wanted to eat outside. In 1980s, Ampera, and Ponyo food stalls transformed their business concept to become restaurants. Then, since the early of 2000s, the earliest generation of Sundanese restaurants started to apply franchise business concept, followed by the emergence of Cibiuk and Manjabal as a new generation of Sundanese restaurants. This article discusses the development of Sundanese restaurants in Bandung since its inception until their transformation become restaurant that had branches in various regions while maintaining their local wisdom values in the midst of the onrushing of modernity. Besides employing historical methods, this article also used the concepts of local cuisine and food industry to understand the development of Sundanese restaurants in Bandung.  Bandung dikenal sebagai salah satu destinasi wisata kuliner utama di Indonesia. Citra kuliner Bandung telah berakar sejak masa kolonial sebagaimana Haryoto Kunto (1986) menjuluki Bandung sebagai “surga tukang jajan”. Salah satu citra kuliner khas Bandung adalah rumah makan Sunda dengan hidangan khasnya. Hidangan Sunda biasa disajikan di lingkungan domestik (rumah tangga). Sejak dekade 1960-an hingga 1970-an, muncul tren warung makan khas Sunda di Bandung, seperti Ampera dan Ponyo. Warung makan Sunda menjadi pilihan bagi masyarakat Pribumi untuk memenuhi kebutuhan selera makan di luar rumah. Pada 1980-an, warung makan Ampera, dan Ponyo mulai bertransformasi menjadi rumah makan. Kemudian, sejak awal tahun 2000-an mulai muncul tren bisnis waralaba (franchise) dalam industri rumah makan Sunda, disertai dengan kemunculan Cibiuk dan Manjabal sebagai generasi baru rumah makan Sunda. Artikel ini membahas perkembangan rumah makan Sunda di Bandung sejak awal kemunculannya hingga bertransformasi menjadi rumah makan besar yang memiliki cabang di berbagai wilayah dengan tetap mempertahankan nilai-nilai kearifan lokal di tengah laju modernitas. Di samping menggunakan metode sejarah, artikel ini juga menggunakan pendekatan local cuisine dan food industry untuk memahami perkembangan rumah makan Sunda di Bandung.